Brachymetatarsia: Review of the literature and report of two cases. Case Report (2015)
Brachymetatarsia is a rare foot disease, defined as the abnormal shortening of the metatarsal bone. It has a 0.02-0.05% incidence and is predominantly in females, with a 25:1 ratio compared to males. There are 3 types: congenital, idiopathic and associated with acquired disorders, being congenital the most common type. The current surgical options available are progressive osseous lengthening with external fixator and osteotomies with acute lengthening, each of them have advantages and disadvantages that should be taken into consideration when choosing one over the other. The following article is a short review of the illness and the report of two cases successfully treated with progressive osseous lengthening with external fixation.